Pengaruh Penggunaan QRIS Terhadap Pola Makan Konsumtif Gen Z Mahasiswa Fakultas Ekonomi Universitas Dharma Andalas - Idwar, Idwar; Yendra, Nofri; Rahmasari, Nisya Cesaryani (Universitas Dharma Andalas, 2025)
The purpose of the study was to determine the effect of perceived ease of use, perceived usefulness, attitude toward using and actual usage on the consumptive eating patterns of gen Z at Faculty Economics and Business Dharma Andalas University partially and simultaneously. Primary data sources from field research and secondary data from library research. The type of research is associative with a quantitative approach. The research population was 357 people, the number of research samples was 200 people determined by purposive sampling with a simple random sampling technique. Data collection methods used questionnaires, interviews and observations. Before the data was processed, it met all instrument tests and classical assumption tests for the research variables perceived ease of use (X1), perceived usefulness (X2), attitude toward using (X3), actual usage (X4) and consumptive eating patterns (Y). The results of multiple linear regression obtained Y = 0.096 + 0.446 X1 + 0.302X2 + 0.279X3 + 0.251X4 + e. The results of partial and simultaneous hypothesis testing at a significance level of 5% show that perceived ease of use, perceived usefulness, attitude toward using and actual usage have a significant positive effect on the consumptive eating patterns of gen Z at Faculty Economics and Business Dharma Andalas University. Abstrak Tujuan penelitian mengetahui pengaruh perceived ease to use, perceived usefullness, attitude toward using dan actual usage terhadap pola makan konsumtif gen Z Fakultas Ekonomi dan Bisnis Universitas Dharma Andalas secara parsial dan simultan. Sumber data primer dari field research dan data sekunder dari library research. Jenis penelitian bersifat asosiatif dengan pendekatan kuantitatif. Populasi penelitian 357 orang, jumlah sampel penelitian 200 orang ditentukan secara purposive sampling dengan teknik simple random sampling. Metode pengumpulan data menggunakan angket, wawancara dan observasi. Sebelum data diolah memenuhi semua uji instrumen dan uji asumsi klasik untuk variabel penelitian perceived ease to use (X1), perceived usefullness (X2), attitude toward using (X3), actual usage (X4) dan pola makan konsumtif (Y). Hasil regresi linier berganda didapat Y = 0.096 + 0.446 X1 + 0.302X2 + 0.279X3 + 0.251X4 + e. Hasil uji hipotesis secara parsial dan simultan pada tingkat signifikansi 5% menunjukkan bahwa perceived ease to use, perceived usefullness, attitude toward using dan actual usage berpengaruh positif signifikan terhadap pola makan konsumtif gen Z Fakultas Ekonomi dan Bisnis Universitas Dharma Andalas.